FORMING STUDENTS' INTEREST IN EXAMPLES OF FICTION LITERATURE THROUGH READING IN READING CLASSES - Ubaydullaevna, Mingbaeva Barno (Miasto Przyszłości, 2023)
this article discusses the formation of students' interest in literary examples through reading in reading classes.